Development of Computerized Adaptive Testing for Emotion Regulation - Xu, Lingling; Jin, Ruyi; Huang, Feifei; Zhou, Yanhui; Li, Zonglong; Zhang, Minqiang (Frontiers in Psychology, 2020)
Emotion regulation (ER) plays a vital role in individuals’ well-being and successful functioning. In this study, we attempted to develop a computerized adaptive testing (CAT) to efficiently evaluate ER, namely the CAT-ER. The initial CAT-ER item bank comprised 154 items from six commonly used ER scales, which were completed by 887 participants recruited in China. We conducted unidimensionality testing, item response theory (IRT) model comparison and selection, and IRT item analysis including local independence, item fit, differential item functioning, and item discrimination. Sixty-three items with good psychometric properties were retained in the final CAT-ER. Then, two CAT simulation studies were implemented to assess the CAT-ER, which revealed that the CAT-ER developed in this study performed reasonably well, considering that it greatly lessened the test items and time without losing measurement accuracy.